2022
DOI: 10.1186/s13287-022-02854-8
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes and autophagy in ocular surface and retinal diseases: new insights into pathophysiology and treatment

Abstract: Background Ocular surface and retinal diseases are widespread problems that cannot be ignored in today’s society. However, existing prevention and treatment still have many shortcomings and limitations, and fail to effectively hinder the occurrence and development of them. Main body The purpose of this review is to give a detailed description of the potential mechanism of exosomes and autophagy. The eukaryotic endomembrane system refers to a range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 112 publications
0
3
0
Order By: Relevance
“…Therefore, corneal transplantation (keratoplasty) has been suggested as an effective therapeutic strategy that can restore vision and corneal integrity ( 64 , 94 ). However, the risk of several complications (particularly immunological rejection) still remains and threatens graft acceptance ( 71 ).…”
Section: Inflammation-related Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, corneal transplantation (keratoplasty) has been suggested as an effective therapeutic strategy that can restore vision and corneal integrity ( 64 , 94 ). However, the risk of several complications (particularly immunological rejection) still remains and threatens graft acceptance ( 71 ).…”
Section: Inflammation-related Diseasesmentioning
confidence: 99%
“…showed that mouse corneal epithelial cell-derived Exos might induce stromal fibroblast differentiation into myofibroblasts and play an essential role in corneal wound healing ( 70 ). Epithelial-derived Exos carry proteins like thrombospondin-2, latent-transforming growth factor beta-binding protein 1, C–X–C motif chemokine 5, and C-C motif chemokine 2, which are involved in wound healing and neovascularization ( 70 , 71 ). Moreover, corneal fibroblasts secrete Exos that contain matrix metalloproteinase 14 (MMP14), which enhances corneal angiogenesis via degenerating vascular endothelial growth factor (VEGF) receptor 1 and VEGF-induced proliferation and migration of endothelial cells ( 72 , 73 ).…”
Section: Inflammation-related Diseasesmentioning
confidence: 99%
“…Autophagy is a highly conserved self-protective mechanism that maintains cellular and metabolic homeostasis by engulfing damaged and senescent organelles or pathogens and encapsulating them into vesicles, fusing them with lysosomes to form autophagic lysosomes, and degrading, recycling, and reusing their internal metabolites (Galluzzi et al, 2017;Dikic and Elazar, 2018). According to the different degradation mechanisms, autophagy can be divided into three types: macroautophagy, microautophagy, and molecular chaperone-mediated autophagy (Andrade-Tomaz et al, 2020;Ma S. et al, 2022). Mitochondrial autophagy (Mitophagy), which belongs to one of the types of macroautophagy and was first proposed by Lemasters in 2005, is an intracellular mechanism of selective degradation targeting dysfunctional mitochondria.…”
Section: Introductionmentioning
confidence: 99%